Pengaruh Rekrutmen Dan Seleksi Terhadap Kinerja Karyawan PT Pos Indonesia (Persero) KC Tangerang Selatan 15400 - Andini, Fahira; Juanda, Angga (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Abstrak. This study aims to determine and analyze whether there is a positive and significant influence of recruitment and selection, both partially and simultaneously, on employee performance at PT Pos Indonesia (Persero) KC Tangerang Selatan 15400. The study uses a quantitative method with a descriptive approach. The sample consists of 129 respondents, which includes the entire employee population, using a saturated sampling technique. The data analysis techniques used are multiple linear regression, t-test, and F-test with the help of SPSS 25.The results of the study show that partially, Recruitment (X1) has a positive and significant effect on employee performance, with a t-value of 4.660 > t-table 1.979 and a significance value of 0.000 < 0.05, thus H1 is accepted. Furthermore, Selection (X2) also has a positive and significant effect on employee performance, with a t-value of 6.273 > t-table 1.979 and a significance value of 0.000 < 0.05, thus H2 is accepted. Simultaneously, Recruitment (X1) and Selection (X2) have a positive and significant effect on employee performance, as indicated by an F-value of 132.574 > F-table 3.07 and a significance value of 0.000 < 0.05. The results of the study produce the multiple regression equation: Y = 10.398 + 0.090X1 + 0.919X2. The regression coefficient value for the Performance variable is 10.398, indicating that if Recruitment (X1) and Selection (X2) remain unchanged, the performance value would be 10.398. The coefficient of determination (R²) is 0.686, which means that Recruitment (X1) and Selection (X2) contribute 68.6% to employee performance, while the remaining 31.4% is influenced by other variables not examined in this study. Therefore, it can be concluded that there is a positive and significant simultaneous effect between the Recruitment and Selection variables on Employee Performance. Keywords: Recruitment, Selection, Employee Performance